An International Comparison on Excessive Credit Expansion, Credit Guarantee Programs and The Risks Arising - TUNAY, KAŞİF BATU (KHAZAR UNIV, 2020)
Crediting in the banking sector plays an important role in all developed and developing countries. For this reason, it is monitored continuously by public authorities and measures are taken to control credit supply in economic growth periods. On the other hand, in an economic slowdown, when banks are reluctant to increase their credit portfolio, public credit guarantee programs are put into use to increase the credit supply. In this study, a sample covering 26 advanced and emerging economies was analyzed, and the effects of credit gap, credit guarantees and economic growth on credits and arising credit risks were investigated. The findings show that both credits and non-performing loans, an important measure of credit risk, are affected by credit gap, credit guarantees, and economic growth. On the one hand, public credit guarantees positively affect economic growth. On the other hand, though they are widely used for supporting small and medium-sized enterprises, our findings suggest that such expansive credit policies might negatively affect the riskiness of the credit portfolios and soundness of the banking sector.
Keywords: credit expansion; credit gap; systemic risk; credit guarantees; procyclicality; FINANCIAL CRISES; EASTERN-EUROPE; PRIVATE-SECTOR; BOOMS; GROWTH; CYCLES